Exploring COVID-19 vaccine hesitancy in unvaccinated adults within a semi-urban population of South India: A qualitative investigation - Dipu T. Sathyapalan; Sivapriya G. Nair; Preetha Prasanna; Appukuttan A; Geethu Sathyan; Hima Joy; Rehana C. Mukundan; Kiran G. Kulirankal; Merlin Moni; Vrinda Nampoothiri (Elsevier, 2024)
Background: Despite broad COVID-19 vaccination coverage in India, hesitancy persists, limiting the achievement of 100 % vaccination coverage across the country to prevent the ongoing transmission of the infection. We explored the key drivers of vaccine hesitancy among unvaccinated adults in semi-urban regions of Kerala, India. Method: ology: Semi-structured face-to-face interviews were conducted from April to May 2022, using purposive sampling to enroll participants with the help of Accredited Social Health Activist (ASHA) workers. Participation in the interviews was voluntary and was conducted at the participant's residence at a time convenient for the participants. Audio files of the interviews were transcribed verbatim, and the anonymized data underwent a multistage thematic analysis using the constant comparative method. Results: In our study with 35 unvaccinated individuals were interviewed. Identified factors for vaccine hesitancy were categorized into different themes: individual factors (35 %), vaccine-related factors (33.33 %), and social/environmental factors (31.67 %). Conclusions: Targeted communication strategies and behavioural change interventions need be employed to mitigate major drivers of vaccine hesitancy. Addressing vaccine hesitancy requires multifaceted strategies including community engagement, collaboration with alternative medical systems, healthcare worker education, prioritizing vulnerable populations, and transparent communication about vaccine safety and adverse events. Implementing these measures will help overcome barriers and enhance vaccine coverage.